Bridelia speciosa Müll.Arg. Stem bark Extracts as a Potential Biomedicine: From Tropical Western Africa to the Pharmacy Shelf - Mohamad Fawzi Mahomoodally; Kouadio Ibrahime Sinan; Kouadio Bene; Gokhan Zengin; Giustino Orlando; Luigi Menghini; Serena Veschi; Annalisa Chiavaroli; Lucia Recinella; Luigi Brunetti; Sheila Leone; Paola Angelini; et al. (MDPI AG, 2020)
Bridelia species have been used in traditional African medicine for the management of diverse human ailments. In the current work, the detailed phytochemical profiles of the extracts of the stem bark of B. speciosa were evaluated and the antioxidant and enzyme inhibitory properties of the extracts were assessed. The anti-bacterial and anti-mycotic effects of the extracts were evaluated against selected pathogen strains. Additionally, the anti-proliferative effects were studied on the liver cancer HepG2 cell line. Finally, the putative protective effects were assessed on isolated rat liver that was challenged with lipopolysaccharide (LPS). The results revealed the presence of 36 compounds in the ethyl acetate extract, 44 in the methanol extract, and 38 in the water extract. Overall, the methanol extract showed the highest antioxidant activity, particularly in LPS-stimulated rat liver. Additionally, this extract exerted the highest antimycotic effect on C. albicans, whereas the water extract showed a promising anti-proliferative effect on liver cancer HepG2 cells. The methanol extract was also the most active as enzyme inhibitor, against acetylcholinesterase and butyrylcholinesterase. The current study appraises the antioxidant and enzyme inhibition properties of B. speciosa methanol extract and showed that this specie could be a promising source of biologically active phytochemicals, with potential health uses.